One Mind: How Our Individual Mind Is Part of a Greater Consciousness and Why It Matters by Larry Dossey - Nelson, Roger D. (Journal of Scientific Exploration, 2014)
<!--[if gte mso 9]> <![endif]--> It seems that every cultural and spiritual tradition has some form of the proposition that we are all part of a greater whole. This goes by many names: Oneness, Unity, Wholeness, Godhead, Brahman, . . . , and it is something philosophers and teachers tell us in many ways. Alan Watts is quoted saying, "You and I are all as much continuous with the physical universe as a wave is continuous with the ocean." Swami Vivikenanda says, "All differences in this world are of degree, and not of kind, because oneness is the secret of everything." And from Osho, "We are all different expressions of one reality, different songs of one singer, different dances of one dancer, different paintings-but the painter is one." Larry Dossey is an integrator, who sees the commonalities and fundamental connections of apparently separate conceptions of the world. He brings this ability to bear in books from which I learn new things and creative ways of thinking about old ones, about ideas that have been around for a long time. It is a talent or a gift he has, but I think, as Edison said, it is 1% inspiration and the rest perspiration. Of course people who are so effective in their work love what they do, so it's no sweat. His most recent book, One Mind, is a gathering and culmination of work by the author, who has touched on the same themes many times before. These are the connections that empower Healing Words and those which underlie The Power of Premonitions, two of his earlier books about ideas that have been on his mind and growing in clarity since his days as a battlefield surgeon in VietNam. Now Dossey is putting it all together, so that his readers can shortcut the process that engages so many of us, trying to integrate our spiritual and experiential lives. He asks who is in charge of the One Mind, and waves away the long list of gods and gurus and recommends to us that "as understanding grows, all descriptions of the Absolute are eventually transcended." <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif";} --> <!--[endif] -->